Evaluation of kinetic for the extraction of bio-active compound (rotenone) from derris elliptica and identification of optimum variables of the exhaustive extraction process - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A.; Ramli, M. K. A.; Latip, R. (2004)
Currently Bio-pesticide is relatively harmless to human and environment and thus desirable for the use in the control of insect vectors. Bio-pesticide have been increasing importance in both scale commercial agriculture and small plot, subsistence farming. One of the sources for bio-pesticide is ‘Tuba’ plant, known as Derris elliptica. Derris elliptica contains bio-active compounds known as rotenone (C23H33O6) which is harmless to plants, highly toxic to many insects and relatively innocuous to mammals. Research carried out was to investigate the optimum independent and dependent variables from the exhaustive rotenone extraction process by evaluating the kinetic equilibrium phase of the Normal Soaking Extraction (NSE) method. The raw plants were collected from Kota Johor Lama, Johor and sorted to collect the root and stem. Only the root and stem were utilized as a raw material of the extraction process. The root and stem were extracted by using the Normal Soaking Extraction (NSE) at ambient temperature of 28 0C to 30 0C with 95 % (v/v) of acetone as a solvent and the solvent-to-solid ratio of the extraction was (10 ml/1g). The extraction was carried out for 24 hours and the fractions of the liquid crude extract were collected for each interval time (30 mins/1.0 ml/fractions) and further cleaned up to remove the fine debris of root and stem prior to determination of rotenone content, % (w/w) and concentration, mg/ml by using the High Performance Liquid Chromatography (HPLC). From the result obtained, it was found that the optimum independent and dependent variables was 10 hours to 12 hours of extraction time, 1.65 % (w/w) rotenone extraction yield, 800 mg to 820 mg of rotenone content and 2800 ppm to 2950 ppm of rotenone concentration respectively.